An automatic platform to monitor Web 2.0 presence of Healthcare Providers in Italy. (13th November 2019) - D'ambrosio, A; Barbara, A; Kakaa, O; Falvo, R; Parente, P; Gualano, M R; Silenzi, A; Siliquini, R
Abstract: Background: Healthcare providers (HP) need to involve the population to spread correct and useful health information and to gather feedback on the perceived quality of the service. Web 2.0, based on the use of Social Networks (SN), allows direct communication between the HP and the population. We built an automatic platform which monitors Web 2.0 usage by Italian public and private HP. Methods: For each HP the platform finds the relative website using Google searches and extracts the links to SN. For Facebook and Twitter, it retrieves one year of content and identifies common topics via natural language processing. Finally, it compares the Web 2.0 usage patterns and topics with the type of HP and geographical position. Results: In 2017, on 540 HP screened 97.8% had a website (309 unique sites, many HP have a common site). 37.5% of the websites had links to SN in the homepage: Youtube (YT) was the most common (74.1%), then Facebook (FB, 72.4%) and Twitter (TW, 51.7%). The presence of SN was lower in the south (OR: 0.63; p < 0.001) while is higher for research centers (OR: 5.12; p < 0.001) and private hospitals (OR: 2.12; p = 0.004). Local Health Trusts were the most active on FB (1.86 more posts, p = 0.004) but research centers had more fans RR: 5.32; p = 0.003) and likes per post (RR: 4.95; p < 0.001). On TW private hospitals had the most followers (RR: 3.35; p = 0.002) and likes per tweet (RR: 3.95; p < 0.001). The most posted topics were on healthy behaviors and organizational changes, while a lower number of posts were on healthy food and vaccines. Posts on specific pathologies information and healthy behaviors received more likes. Conclusions: We propose an automatic platform that monitors the internet presence of HP in Italy, helping to define the best strategies for effective health communication. We found that in the south and in the public sector the importance of this tool is less perceived, with a lower SN presence and a gap between posted topics and those appreciated by the public. Key messages: We propose an automatic platform that reports and monitors the web 2.0 presence and usage by HP in Italy, helping to define the best strategies to spread effective health communication. In Italy the presence of SN among HP is lower in the south and in the public, while is higher for research centers. HP have to engage the population maximizing the potentiality of web 2.0.